Prevalencia De Alteraciones En El Desarrollo Psicomotor Para Niños De 1 Mes A 5 Años Valorados Con La Prueba EDI En Un Centro De Salud En México En El Periodo Febrero A Noviembre De 2015 - Callejas, Kevin Bryan Tirado; Mejí, Laura Maricela Arvizu; Pacheco, María Andrea Martínez; Peña, María de Lourdes Guerrero; Sánchez, Luis Eduardo Contreras; Malagón, Genaro Vega; Argenis, Gustavo; Segura, Hernández (European Scientific Journal, ESJ, 2017)
Objective: To establish the prevalence of the psychomotor development alterations in children from a month old up to 5 years old tested with EDI test. Methodology: Transversal study with a non probabilistic sample of children who entered to be evaluated with EDI test for the first time in a period from February to November 2015. It took 204 evaluations through the SPSS V program. Results: 54 (26.47%) children resulted with some alert data, in which 32 (59.26%) referred lag in their development and 22 (40.74%) with risk of development delay. The rest were 150 (73.53%) tests with normal development. Conclusions: The high index of urinary tract infections during the prenatal period such as the preterm births stimulates the prevalence of psychomotor development alterations, which is why it is important the correct manage during pregnancy.